A semi-Lagrangian view of ozone production tendency in North American outflow in the summers of 2009 and 2010 - B. Zhang; R. C. Owen; J. A. Perlinger; A. Kumar; S. Wu; M. Val Martin; L. Kramer; D. Helmig; R. E. Honrath (Atmospheric Chemistry and Physics, 2014)
The Pico Mountain Observatory, located at 2225 m a.s.l. in the Azores Islands, was established in 2001 to observe long-range transport from North America to the central North Atlantic. In previous research conducted at the observatory, ozone enhancement (> 55 ppbv) in North American outflows was observed, and efficient ozone production in these outflows was postulated. This study is focused on determining the causes for high d [O 3 ] / d [CO] values (~1 ppbv ppbv −1 ) observed in the summers of 2009 and 2010. The folded retroplume technique, developed by Owen and Honrath (2009), was applied to combine upwind FLEXPART transport pathways with GEOS-Chem chemical fields. The folded result provides a semi-Lagrangian view of polluted North American outflow in terms of physical properties and chemical processes, including production/loss rate of ozone and NO x produced by lightning and thermal decomposition of peroxy acetyl nitrate (PAN). Two transport events from North America were identified for detailed analysis. High d [O 3 ] / d [CO] was observed in both events, but due to differing transport mechanisms, ozone production tendency differed between the two. A layer of net ozone production was found at 2 km a.s.l. over the Azores in the first event plume, apparently driven by PAN decomposition during subsidence of air mass in the Azores–Bermuda High. In the second event, net ozone loss occurred during transport in the lower free troposphere, yet observed d [O 3 ] / d [CO] was high. We estimate that in both events, CO loss through oxidation contributed significantly to d [O 3 ] / d [CO] enhancement. Thus, it is not appropriate to use CO as a passive tracer of pollution in these events. In general, use of d [O 3 ] / d [CO] as an indicator of net ozone production/loss may be invalid for any situation in which oxidants are elevated. Based on our analysis, use of d [O 3 ] / d [CO] to diagnose ozone enhancement without verifying the assumption of negligible CO loss is not advisable.